2011
DOI: 10.1074/jbc.m111.283580
|View full text |Cite
|
Sign up to set email alerts
|

Collapsin Response Mediator Proteins (CRMPs) Are a New Class of Microtubule-associated Protein (MAP) That Selectively Interacts with Assembled Microtubules via a Taxol-sensitive Binding Interaction

Abstract: Background: CRMPs play roles in axon specification and semaphorin 3A-induced growth cone collapse, but their biochemical function is unclear. Results: CRMPs are found to bind directly to microtubules through a conserved C-terminal region. Conclusion: CRMPs can stabilize microtubules but are negatively regulated by phosphorylation. Significance: This work can explain phenotypes associated with loss of CRMPs on axon specification and dendritic arborization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 75 publications
4
77
0
1
Order By: Relevance
“…During the metaphase, the mitotic spindle rotates and is anchored to the lateral cell cortex via dedicated proteins by astral microtubules, and then defining the apicobasal orientation of the division plane 1,46 . Interestingly, previous work showed that CRMP2 is specifically associated with spindle and astral microtubules and that CRMP2 knockdown alters astralmicrotubule stability 37,42 . In this study, we demonstrate that proper CRMP2 activity is required for astral fibre organization and mitotic spindle positioning during metaphase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the metaphase, the mitotic spindle rotates and is anchored to the lateral cell cortex via dedicated proteins by astral microtubules, and then defining the apicobasal orientation of the division plane 1,46 . Interestingly, previous work showed that CRMP2 is specifically associated with spindle and astral microtubules and that CRMP2 knockdown alters astralmicrotubule stability 37,42 . In this study, we demonstrate that proper CRMP2 activity is required for astral fibre organization and mitotic spindle positioning during metaphase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in Semaphorinmediated axon guidance, glycogen-synthase Kinase 3b (GSK3b) inactivates through phosphorylation the collapsin response mediator protein 2 (CRMP2), a microtubule-stabilizing protein, thus favouring microtubule depolymerization [33][34][35] . Several lines of evidence implicate GSK3b in regulating astral microtubule NATURE COMMUNICATIONS | DOI: 10.1038/ncomms7366 ARTICLE dynamics and spindle orientation 36,37 . CRMP members interact with dynein 38,39 , a molecular motor also involved in spindle orientation.…”
Section: Apicobasal Orientation Of Progenitor Division Is Stereotypedmentioning
confidence: 99%
“…The C-terminal phosphorylation of CRMP2 by Cdk5 and GSK3b attenuates the interaction between CRMP2 and tubulin heterodimer 10,13 . Lin et al reported that the phosphorylation of CRMP1/2 C terminal by GSK3b attenuates the interaction of CRMP1/2 and microtubules 44 . We found that CRMP1(S522D), a Cdk5-phosphor mimicking mutant, bound Filamin-A with higher affinity than CRMP1 wild type (Fig.…”
Section: Crmp1 Regulates the Interaction Of Filamin-a And F-actinmentioning
confidence: 99%
“…CRMP2 has been shown to enhance microtubule polymerization, whereas CRMP3 and CRMP5 inhibit the process (21,22,(43)(44)(45). CRMP4 binds directly to tubulin, but its effects on microtubule assembly have not been tested (18,21,46). We generated GST fusion proteins for the short isoform of CRMP4 and for a series of CRMP4 deletion mutants to test the effect of CRMP4 in microtubule assembly in vitro and to map the regions of CRMP4 responsible for this activity (Fig.…”
Section: Crmp4 Promotes Growth Cone Spreading and Axonmentioning
confidence: 99%